Augmented Renal Clearance Using Population-Based Pharmacokinetic Modeling in Critically Ill Pediatric Patients*. Issue 9 (September 2017) - Avedissian, Sean N.; Bradley, Erin; Zhang, Diana; Bradley, John S.; Nazer, Lama H.; Tran, Tri M.; Nguyen, Austin; Le, Jennifer
Abstract : Objectives: The objectives of this study were to: 1) evaluate the prevalence of augmented renal clearance in critically ill pediatric patients using vancomycin clearance; 2) derive the pharmacokinetic model that best describes vancomycin clearance in critically ill pediatric patients; and 3) correlate vancomycin clearance with creatinine clearance estimated by modified Schwartz or Cockcroft-Gault. Design: Retrospective, two-center, cohort study from 2003 to 2016. Setting: Clinical drug monitoring services in the PICUs at two tertiary care, teaching hospitals. Patients: Children from 1 to 21 years old. Interventions: None. Measurements and Main Results: Identify patients with augmented renal clearance (vancomycin clearance ≥ 130 mL/min/1.73 m 2 used as definition of augmented renal clearance). Derive final population-based pharmacokinetic model and estimate individual patient pharmacokinetic parameters. Compare estimated glomerular filtration rate (modified Schwartz or Cockcroft-Gault depending on age < or ≥ 17 yr) with vancomycin clearance. Augmented renal clearance was identified in 12% of 250 total subjects. The final population-based pharmacokinetic model for vancomycin clearance (L/hr) was 0.118 × weight (e –1.13 × [serum creatinine (Scr) – 0.40] ). Median vancomycin clearance in those with versus without augmented renal clearance were 141.3 and 91.7 mL/min/1.73 m 2, respectively ( p < 0.001). By classification and regression tree analysis, patients who were more than 7.9 years old were significantly more likely to experience augmented renal clearance (17% vs 4.6% in those ⩽ 7.9 yr old; p = 0.002). In patients with augmented renal clearance, 79% of 29 had vancomycin trough concentrations less than 10 µg/mL, compared with 52% of 221 in those without augmented renal clearance ( p < 0.001). Vancomycin clearance was weakly correlated to the glomerular filtration rate estimated by the modified Schwartz or Cockcroft-Gault method (Spearman R 2 = 0.083). Conclusions: Augmented renal clearance was identified in one of 10 critically ill pediatric patients using vancomycin clearance, with an increase of approximately 50 mL/min/1.73 m 2 in those with augmented renal clearance. As augmented renal clearance results in subtherapeutic antibiotic concentrations, optimal dosing is essential in those exhibiting augmented renal clearance. Abstract : Supplemental Digital Content is available in the text.